A service industry perspective on software defined radio access networks. (2017) - DeCusatis, Casimer; Papapanagiotou, Ioannis
Despite the rapid growth of service science, relatively little attention has been paid to the service architecture requirements in software defined radio access networks (SDRAN). In this concept paper, we propose to repurpose cloud computing network services to address issues specific to SDRAN. In particular, a multi-level backhaul slicing approach derived from cloud computing networks is discussed as a way to mitigate interference limited networks with a frequency reuse factor of one. Experimental demonstration of the control plane implementation in a virtual cloud network is presented, and implications on service provider development and training are also discussed.